DESIGNING METACOGNITIVE LEARNING STRATEGY FOR IMPROVING VOCABULARY MASTERY THROUGH MUSICAL INTELLIGENCE - Nila Sari Dewi (University of Sang Bumi Ruwa Jurai, 2017)
The objective of this research was to describe; (1). The design of learning English strategy by using metacognitive for improving vocabulary mastery through musical intelligence, (2). the system of learning evaluation , and (3). The improvement of students vocabulary learning achievement. The methodology of this research was qualitative research that involved students of Economic faculty who took English level II at language laboratory of Bandar Lampung University in period 2016/2017. The writer took the class by using random sampling from four classes of Economic students, that was 20 students. This metacognitive learning designed students activities as listening to the song in audio and doing the task (cloze procedure), reading the text of song through audio visual and practising good pronunciations, understanding words and sentences meanings, producing sentences in a good structure, retelling the content of song in written form and spoken form in a short dialogue. Here, students learnt vocabulary mastery while practising integrated skills (listening, speaking, reading, and writing) ang English components (vocabulary, structure and pronunciation). The instruments of research were observation and final test. The research findings indicated that; (1) applying the design of metacognitive learning strategy made an improvement of active students in learning activities about 18 students or 90%, (2). The learning evaluation used Simpel PAS (Sistem Pengelolaan Program Analisis Soal). In the first test, the validity was 0,2 (low), the test reliability was was 0,59 (moderate), the level of difficulty was 0,54(moderate) and the discrimination power was 0,36 (moderate). In the second test, the test validity was 0,41 (moderate), the test reliability was 0,78 (high), the level of difficulty was 0,68 (moderate) and the discrimination power was 0,36 (moderate), (3). the achievement of vocabulary mastery in the first test, students who passed the test was 12 students or 60%. The second test, students who passed the test were 16 students or 80%. So, there was an improvement of students vocabulary learning achievement. This findings indicated that this learninng strategy design can improve students learning in voabulary mastery effectively.